The many faces of neonatal Herpes simplex infection. A case series of 4 neonates. - Mann, J.; Rabindranathnambi, A.; Ravenscroft, J. (European Journal of Pediatric Dermatology, 2021)
Neonatal Herpes simplex virus (HSV) infection is a potentially life threatening disease. We describe a case series of 4 neonates who demonstrate variable presentations of neonatal cutaneous HSV and the difficulties that can occur in diagnosis. Our aim is to increase awareness of the clinical variation in neonatal HSV to facilitate early diagnosis, prompt treatment and improved outcomes.